2014
DOI: 10.1371/journal.pone.0115767
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminocardiac Reflex by Mandibular Extension on Rat Pial Microcirculation: Role of Nitric Oxide

Abstract: In the present study we have extended our previous findings about the effects of 10 minutes of passive mandibular extension in anesthetized Wistar rats. By prolonging the observation time to 3 hours, we showed that 10 minutes mandibular extension caused a significant reduction of the mean arterial blood pressure and heart rate respect to baseline values, which persisted up to 160 minutes after mandibular extension. These effects were accompanied by a characteristic biphasic response of pial arterioles: during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 34 publications
5
26
0
Order By: Relevance
“…Previous data, in normotensive rats, demonstrated that a single brief (10 min) and passive ME caused a significant and prolonged decrease of MABP and HR and, in pial arterioles, a decrease of the diameter concomitant to ME followed by an increase after removing ME. Interestingly, these arteriolar responses have been found to be mediated by different mechanisms (Lapi et al, 2013 , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous data, in normotensive rats, demonstrated that a single brief (10 min) and passive ME caused a significant and prolonged decrease of MABP and HR and, in pial arterioles, a decrease of the diameter concomitant to ME followed by an increase after removing ME. Interestingly, these arteriolar responses have been found to be mediated by different mechanisms (Lapi et al, 2013 , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mandibular extension (ME) was induced as previously described (Lapi et al, 2014 ). Briefly, an appropriately U-shaped spring device was placed between the superior and inferior dental arches of the rat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 , 8 , 12 , 27 28 , 45 67 In another context, it could been shown that the gender has an important influence on pituitary adenomas; especially in frequency and in disease patterns. 26 , 32 34 , 36 , 39 , 46 But for the TCR nothing is known about a gender-dependence in pituitary adenoma function. However, the effects of such adverse events as induced by the TCR on postoperative pituitary function have never been explored as well.…”
Section: Introductionmentioning
confidence: 99%